Mesopredators retain their fear of humans across a development gradient. (10th January 2022) - Reilly, Chloe M; Suraci, Justin P; Smith, Justine A; Wang, Yiwei; Wilmers, Christopher C
Abstract: Anthropogenic impacts on wildlife behavior arise both from the immediate presence of people, which induces fear responses in many species, and the human footprint (i.e., landscape modification such as residential development), which affects animal movement and habitat use. Where both disturbance types co-occur, disentangling their impacts remains a challenge. Disturbance effects may interact such that species respond to increased human footprint by either reducing (habituation) or increasing (sensitization) avoidance of human presence. We experimentally manipulated perceived human presence, using playbacks of people talking, across a gradient of human footprint in California's Santa Cruz Mountains and used camera traps to quantify the behavioral responses of bobcats ( Lynx rufus ), striped skunks ( Mephitis mephitis ), and Virginia opossums ( Didelphis virginiana ), mesopredators known to exhibit strong fear response to human presence but which vary in their use of developed areas. Bobcats and skunks reduced activity in response to human playbacks but showed no change in responsiveness to playbacks across the gradient of human footprint, suggesting that these species are similarly fearful of humans at all development levels tested. Opossums exhibited a significant interaction between human footprint and playback treatment such that reductions in activity level in response to human playbacks were strongest at higher levels of building density. Our results indicate that, rather than habituating to human presence, some mesopredators retain a strong fear of humans or become more fearful when inhabiting more developed areas. We suggest that consistently high responsiveness to immediate human presence may benefit mesopredators living in human-dominated landscapes by mitigating the risk of anthropogenic mortality. Abstract : Mesopredators remain fearful of humans, whether they are in remote, protected areas, or in the backyards of densely populated suburbs. Using an experimental approach, we show that bobcats and striped skunks exhibit a consistent fear response to people, regardless of level of human footprint. Meanwhile, Virginia opossums exhibit heightened fear in areas of high human disturbance. Maintaining a strong fear response to humans may help mesopredators coexist in human-dominated landscapes.